Andar com fé eu vou: avaliação das estratégias de turistificação da cidade de Juazeiro do Norte a partir das romarias (2000-2020) - Oliveira, Bárbara Almeida (2023)
In the last two decades, Juazeiro do Norte has been integrating national and state trends that adopt a developmental paradigm of tourist activity as an articulating element of the local development. In the case of Juazeiro do Norte, the pilgrimages that occur since 1889 became after the 1970s the main raw material in the development of the sector. However, it has been visualized, that this process has been getting significant space in the field of urban planning. Therefore, it is defined as a general objective to evaluate the strategies of turistification of Juazeiro do Norte from the operationalization of the pilgrimages as an object of urban planning. To this end, we followed the perspective of in-depth evaluation based on the propositions of Lea Rodrigues (2011, 2016). Through a qualitative approach, four different data collection strategies were used (bibliographic, documental, iconographic, and interviews) with the purpose of covering different dimensions of in-depth evaluation. The research led us to understand that it will be in the field of urban planning that convergent actions will be defined for the re-functionalization of certain spaces in the city, aimed at meeting dynamics of religious tourism. In this context, the public power (town and state) is identified as the main agents in the rationalization and re-functionalization of the Holy City into a Tourist City. It was also observed that the urban intervention projects called ‘Roteiro da Fé’ (Route of Faith) approved in 2000 and 2009, constitute milestones of this state action by reinforcing strategic actions in the adequacy of the city to the dynamics of tourism. They are sustained in constitution of a basic infrastructure (Adequate City), aggrandizement of spaces (Monument City) and in material maintenance of identity of the space (Historical City). Although the coexistence of these "cities", there were also structural deficiencies that could not be solved even more than twenty years after the approval of the Master Plan. The lack of a public policy for municipal tourism, the constitution of a database about the impact of the pilgrimages in the municipality and its communicability with different interest groups are still necessary, especially if we consider that the phenomenon is at the base of territorial and economic formation of city